2015
DOI: 10.1007/s00246-015-1173-x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel TBX1 Loss-of-Function Mutation Associated with Congenital Heart Disease

Abstract: Congenital heart disease (CHD) is the most prevalent type of birth defect in humans and is the leading non-infectious cause of infant death worldwide. There is a growing body of evidence demonstrating that genetic defects play an important role in the pathogenesis of CHD. However, CHD is a genetically heterogeneous disease and the genetic basis underpinning CHD in an overwhelming majority of patients remains unclear. In this study, the coding exons and splice junction sites of the TBX1 gene, which encodes a T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 87 publications
2
17
0
Order By: Relevance
“…The index patient had a family history of CHD and genetic analysis indicated that the mutation co-segregated with VSD transmitted in an autosomal dominant pattern with complete penetrance. Biochemical analysis revealed that Q277X-mutant TBX1 lost transcriptional activating function when compared with its wild-type counterpart (4). Taken together, these results, together with those of the present study, support that genetically compromised TBX1 confers an enhanced susceptibility of CTD in a minority of cases.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The index patient had a family history of CHD and genetic analysis indicated that the mutation co-segregated with VSD transmitted in an autosomal dominant pattern with complete penetrance. Biochemical analysis revealed that Q277X-mutant TBX1 lost transcriptional activating function when compared with its wild-type counterpart (4). Taken together, these results, together with those of the present study, support that genetically compromised TBX1 confers an enhanced susceptibility of CTD in a minority of cases.…”
Section: Discussionsupporting
confidence: 86%
“…Heterozygous TBX1-null mice exhibit cardiac, craniofacial, thymic and parathyroid deformities, similar to those observed in patients with severe 22q11DS (50)(51)(52). In addition to syndromic CTD, TBX1 mutations have been causally linked to non-syndromic CTD in humans, including isolated TOF, VSD, PA, DORV, IAA and aortic arch anomalies (4,(53)(54)(55). However, the prevalence and spectrum of TBX1 mutations in patients with other forms of non-syndromic CTD remain unknown.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Deleterious variants located within the Brachyury T domain (a well-conserved DBD, shared with T-Box family members) are associated with DGS/VCFS (figure 3 and online supplementary table S2) and some variants are associated with isolated congenital heart defects (CHDs) (figure 3 and online supplementary table S2). In vitro investigations by luciferase assay demonstrated that the only identified PTC in the DNA-binding domain of TBX1 p.Glu277*, which co-segregated in a family with CHD, is a LoF variant 33. This variant is distal to our p.Arg269* variant, which manifests as isolated VPI without any cardiac defect.…”
Section: Discussionmentioning
confidence: 95%
“…TBX1 mutation can lead to DiGeorge syndrome (DGS), which is the most common microdeletion syndrome, and is characterized by congenital cardiac, craniofacial and immune system abnormalities (105). Additionally, Pan et al reported that a novel heterozygous TBX1 mutation, p.Q277X, was identified in an index patient with double outlet right ventricle and ventricular septal defect (106). TBX2 gene is expressed in the myocardium of the atrioventricular canal, outflow tract and inflow tract and plays a critical role in heart chamber formation (107).…”
Section: H3k4 Methylation and Chdmentioning
confidence: 99%